Stimulus To Improve Customer Experience In Indonesia's Cargo Shipping Service Industry - Wijayanto, Yeremia; Ardoko, Prono; Hapsari, Pamungkas (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
Studies on customer experience have many links between stimuli and customer responses: cognitive, affective, social, physical, and sensory. Still, there have not been many in-depth studies on how these stimuli are obtained due to the limited empirical studies on stimuli that can affect customer experience. This research was conducted to identify and assess the most potent stimulus influencing customer experience in Indonesia's cargo shipping service industry. The Analytic Hierarchy Process (AHP) technique evaluated the significance of the customer experience stimulus criteria and sub-criteria. Nine senior managers with experience in the cargo shipping industry were asked to participate in this research. The results show that the internal stimulus has the most decisive importance, followed by the dynamic interaction between the stimulus and the external stimulus. Globally, the calculation results reveal that the elements of service quality, company capabilities, and communication processes have a high weight compared to other elements that make up the customer experience stimulus. At the end of the study, the theoretical and managerial implications and recommendations for further research are presented.